Psychology of Perception - Grondin, Simon (Springer, 2016)
This book is a translation of “Psychologie de la perception” published by the Presses de l’Université Laval and has the same name as a course offered at the School of Psychology of Laval University, Québec. It is not a coincidence; the book was written for students of this course. Over the years, whether at Laurentian University a few decades ago or at Laval University since 1996, I learned a lot from the questions and needs for clarifi cation voiced by the students. The book is partly a response to the requested explanations regarding some of the main phenomena, techniques, and principles encountered in the fi eld of perception. I would like to thank Anne-Marie Grondin who produced numerous illustrations contained in this book; Tsuyoshi Kuroda, expert in psychoacoustics, who provided many tips and some fi gures in the preparation of Chaps. 2 and 3; and Daniel Voyer of the University of New Brunswick for his fi ne revision of the content.